2005
DOI: 10.1007/bf03347203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex steroids on expression of adenylyl cyclase messenger RNA in rat uterus

Abstract: The aim of our study was to investigate the effects of estradiol (E2) and/or progesterone (P4) bilateral ovariectomized rats on gene expressions of adenylyl cyclases (AC2, AC4, AC6, AC9). Non-pregnant (NP) Wister rats (between post-natal 10 and 12 weeks) and normal pregnant rats (between postnatal 10 and 14 weeks) were used. NP rats were divided into five groups: 1) control NP rats, 2) ovariectomy rats (OVX), 3) OVX injected with E2 (6 microg) for 4 days (E2), 4) OVX injected with P4 (5 mg) for 4 days (P4), 5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Estradiol positively regulated cAMP signalling in a variety of cell types, for example, in rat cardiomyocytes (Buitrago et al ., ) or coronary artery smooth muscle cells (Yu et al ., ), through non‐genomic action of plasmalemmal ER on the tmAC activity. Similarly, the limited data demonstrating a genomic action of estradiol on cAMP signalling support its positive regulatory effect (Asano et al ., ; Ismail et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Estradiol positively regulated cAMP signalling in a variety of cell types, for example, in rat cardiomyocytes (Buitrago et al ., ) or coronary artery smooth muscle cells (Yu et al ., ), through non‐genomic action of plasmalemmal ER on the tmAC activity. Similarly, the limited data demonstrating a genomic action of estradiol on cAMP signalling support its positive regulatory effect (Asano et al ., ; Ismail et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…CDKN1A (p21), as a G 1 phase regulatory protein, inactivates the CDK4-cyclin complex by binding to it, leading to cell cycle stagnation in the G 1 phase [ 45 ]. An animal experiment [ 46 ] has proved that the expression of p21 in osteoblasts was significantly increased in rats after ovariectomy ( P < 0.01). It is also reported that the downregulation of p21 protein expression can promote the proliferation of osteoblasts [ 45 ].…”
Section: Discussionmentioning
confidence: 99%